Innovation and Technology needs for the oil and gas industry in Peru - Barriga P, Christ; Aliaga G. , Lesly; Bermejo N., Jorge; Catari C., Pamela; Martinez S., Romina; Valdivia Ch., Mauricio (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Peru experienced the oil rush due to the discovery of reserves, but since the Camisea project was found in the Cuzco region, oil has been in decline, Peru is rated too low competitiveness rates below countries such as Ecuador and Colombia. The hydrocarbons sector accounted for 54% of the total energy tender in 2012. The oil and gas industry has advanced technologically. Today, the technological challenges are focused on taking advantage of unconventional resources having a strong focus on process safety, environmental management, and fuel quality. In a new era of high volatility in the oil and gas price, technology is crucial to maximizing the value; among them, the Modernization Project of the Talara Refinery and its process is announced. Peru is perfecting technologies to take advantage of gas and oil that are difficult to access so that its role in the Peruvian economy is fundamental.